Efficient transmutation of long-lived fission products in a Gamma Factory beam driven advanced nuclear energy system - Baolong Hu; Mieczyslaw Witold Krasny; Wiesław Płaczek; Yun Yuan; Xiaoming Shi; Kaijun Luo; Wen Luo (Scientific Reports)
Abstract The Gamma Factory (GF) project aims to generate high-intensity $$γ$$ -ray beams of tunable energy and relatively small energy spread. Such beams can be optimized to generate an intense photo-neutron source, capable of driving an advanced nuclear energy system (ANES) for nuclear waste transmutation and supplying electrical power that is necessary for the GF operation mode of the Large Hadron Collider storage ring. In this study, we investigate the feasibility of driving ANES with the GF beam which is optimized to maximize the neutron production rate. The dependence of the ANES thermal power on the distance between the positions of the ANES and the GF $$γ$$ -ray source is evaluated. For the $$γ$$ -ray beam reaching the intensity of $$\sim 10^{19}$$ photons per second, the ANES thermal power could exceed 500 MWt. Under the assumption that ANES operates over 20 years, the transmutation rate could reach $$30%$$ for five typical long-lived fission products (LLFPs): $$^{79}$$ Se, $$^{99}$$ Tc, $$^{107}$$ Pd, $$^{129}$$ I, $$^{137}$$ Cs. Our comparative studies show that although the neutron production efficiency of the GF $$γ$$ -ray beam (per MW of the beam power) is approximately 14 times lower than that of the 500 MeV proton beam, the overall net ANES power production efficiency for the GF beam driver scheme could be comparable to that of the proton beam driver scheme, while providing additional transmutation capacity, not available for the proton beam driven scheme. It is suggested that the GF-driven ANES could provide a viable solution for the efficient transmutation of the loaded LLFPs with no prior isotopic separation, and generate the requisite electrical power for its operation, with reduced production of LLFPs over its operation cycle.